Strategi Pencapaian Kemandirian Pesantren Tradisional sebagai Upaya Transformasi Layanan Umat pada Kantor Kementerian Agama Kabupaten Kendal - Kusuma Chrisantina, Vita Santa (JURNAL ILMIAH GEMA PERENCANA, 2022)
Islamic boarding schools or pondok pesantren are non-formal educational institutions that have the characteristics of simplicity, obedience to the kyai, tenacity, independence and having social spirit. However, the independence of pondok pesantren is not only a way of life for students, but pondok pesantren must be able to empower the community with entrepreneurship so that economic independence can be realized. The Ministry of Religious Affair as an institution for fostering pondok pesantren has limitations in guiding and mentoring, especially to realize pondok pesantren independence. Thus the purpose of this paper is to provide a reference in the form of an implementable strategy to realize the independence of traditional pondok pesantren so that they can realize the transformation of people’s services. This research was conducted using a qualitative approach. Data analysis was carried out by SWOT analysis. The results of this study are 1) the independence of pondok pesantren can be realized by using a combination of strength and threat analysis strategies with a weight of 3.2; 2) priority activities are implementing entrepreneurship in tandem with learning, applying the principles of prudence, transparency and accountability as well as conducting risk analysis. Conclusion: The independence of pondok pesantren is not only to improve the quality of santri in terms of independence in carrying out the learning process, but also economic independence and community empowerment by improving the quality of life through improving the quality of the economy.